Developing The M6 Learning Model to Improve Mathematic Critical Thinking Skills - Susandi, Ardi Dwi; Sa’dijah, Cholis; As’ari, Abdur Rahman; Susiswo, Susiswo (Pedagogika, 2023)
This research & development aims to develop and produce quality learning models. The main product in this study is the M6 learning model which has the following syntax: (1) focusing on initial skills; (2) justifying concepts; (3) investigating problems; (4) presenting ideas; (5) evaluating; and (6) concluding. The results show that the M6 learning model developed meets the validity requirements. This study concludes that the M6 learning model has met the requirements by the assessment of experts so that it can improve students‘ critical thinking skills.